Sony vs Toshiba : the fog of a format war obscured a complicated high definition landscape - Elias, Jaan, (SAGE knowledge. Cases., 2016)
In August of 2005, Sony and Toshiba suspended talks aimed at creating a unified standard for the next-generation, high definition DVD format. This case examines the issues which marked the differences between the two companies.